Investigating Delays in Libyan Road Construction Projects Using Structural Equation Modelling (SEM) - Ismail, Amiruddin; Y. Y. Alfakhri, Aboubaker.; Azry Khoiry, Muhamad; M Abdelsalam, Hassan; Elhub, B (International Journal of Engineering and Technology, 2018)
Transportation infrastructure, specifically road projects, is the backbone of economic and social development of many countries. Successful road infrastructure projects are delivered with reduced cost, on time. Factors contributing to Construction delay in road construction projects in Libya were identified and ranked through a questionnaire survey distributed to owners, consultants, and contractors involved in road projects. A total of 256 completed questionnaire forms were received and analysed. A Structural Equation Modelling SEM Path Model of relationship between delay factors and effects in road construction was formulated and evaluated using [SEM] 21 software.Â 49 factors classified into eight groups of factors and three groups of effects of delay. The contractor group in delay factors had the greatest impact on road construction delay with path coefficient Î²-values of 0.249, while financial groups in delay effects had the greatest impact on road construction delay with path coefficient Î²-values of 0.88. The R2 value of the model is 0.48, indicating that the developed model substantially explains Construction delay. This rigorous multivariate analysis has identified several causative factors that contribute to delay in road construction projects in Libya. The findings will help all parties involved in construction projects to achieve better control over construction delays, and will provide support for practitioners to incorporate risk analysis for potential Construction delay in future projects. As well as for researchers in the field of road construction and understanding of the factors causing project cost overruns in developing countries.Â Â